Matematyka

Autorzy:Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Rozwiąż równanie 4.56 gwiazdek na podstawie 9 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a)\ (x+1)^2+6x=(x-1)^2` 

`\ \ \ x^2+2x+1+6x=x^2-2x+1` 

` \ \ \ x^2+8x+1=x^2-2x+1\ \ \ |-x^2-1` 

` \ \ \ 8x=-2x \ \ \|+2x`  

`\ \ \ 10x=0\ \ \ |:10` 

`\ \ \ x=0` 

 

`b)\ (x-2)(x+2)+3x=(4+x)(x-4)` 

`\ \ \ x^2-2^2+3x=(x+4)(x-4)` 

`\ \ \ x^2-4+3x=x^2-4^2` 

`\ \ \ x^2+3x-4=x^2-16\ \ \ |-x^2` 

`\ \ \ 3x-4=-16\ \ \ |+4` 

`\ \ \ 3x=-12\ \ \ |:3` 

`\ \ \ x=-4` 

 

`c)\ (4x-1)^2+18x=16(x-3)(x+3)` 

`\ \ \ 16x^2-8x+1+18x=16(x^2-3^2)` 

`\ \ \ 16x^2+10x+1=16(x^2-9)` 

`\ \ \ 16x^2+10x+1=16x^2-144\ \ \ |-16x^2` 

`\ \ \ 10x+1=-144\ \ \ |-1` 

`\ \ \ 10x=-145\ \ \ |:10` 

`\ \ \ x=-14,5` 

 

`d)\ (x-9)^2-(x+9)^2=(x+3)^2-(x-3)^2` 

`\ \ \ x^2-18x+81-(x^2+18x+81)=x^2+6x+9-(x^2-6x+9)` 

`\ \ \ x^2-18x+81-x^2-18x-81=x^2+6x+9-x^2+6x-9` 

`\ \ \ -36x=12x\ \ \ |+36x` 

`\ \ \ 48x=0\ \ \ |:48` 

`\ \ \ x=0` 

 

`e)\ x^2-(5-x)^2=4x^2-(2x-1)(2x+1)` 

`\ \ \ x^2-(25-10x+x^2)=4x^2-(4x^2-1)` 

`\ \ \ x^2-25+10x-x^2=4x^2-4x+1` 

`\ \ \ 10x-25=1\ \ \ |+25` 

`\ \ \ 10x=26\ \ \ |:10` 

`\ \ \ x=2,6`